Overexpression of a Modified Plant Thionin Enhances Disease Resistance to Citrus Canker and Huanglongbing (HLB) - Hao, Guixia; Stover, Ed; Gupta, Goutam (Frontiers in Plant Science, 2016)
Huanglongbing (HLB or citrus greening disease) caused by Candidatus Liberibacter asiaticus (Las) is a great threat to the US citrus industry. There are no proven strategies to eliminate HLB disease and no cultivar has been identified with strong HLB resistance. Citrus canker is also an economically important disease associated with a bacterial pathogen (Xanthomonas citri). In this study, we characterized endogenous citrus thionins and investigated their expression in different citrus tissues. Since no HLB-resistant citrus cultivars have been identified, we attempted to develop citrus resistant to both HLB and citrus canker through overexpression of a modified plant thionin. To improve effectiveness for disease resistance, we modified and synthesized the sequence encoding a plant thionin and cloned into the binary vector pBinPlus/ARS. The construct was then introduced into Agrobacterium strain EHA105 for citrus transformation. Transgenic Carrizo plants expressing the modified plant thionin were generated by Agrobacterium-mediated transformation. Successful transformation and transgene gene expression was confirmed by molecular analysis. Transgenic Carrizo plants expressing the modified thionin gene were challenged with X. citri 3213 at a range of concentrations, and a significant reduction in canker symptoms and a decrease in bacterial growth were demonstrated compared to nontransgenic plants. Furthermore the transgenic citrus plants were challenged with HLB via graft inoculation. Our results showed significant Las titer reduction in roots of transgenic Carrizo compared with control plants and reduced scion Las titer twelve months after graft inoculation. These data provide promise for engineering citrus disease resistance against HLB and canker.